Bacterial load and chemical pollution level of the River Buriganga, Dhaka, Bangladesh - Saha, Mihir Lal; Khan, Mahbubar Rahman; Ali, Mohammad; Hoque, Sirajul (Bangladesh Journal of Botany, 2010)
The River Buriganga is the life line of the Dhaka city and flanked in its southern side. The aerobic heterotrophic bacterial count of the River Buriganga was found to be in the range of 1.0 × 105 to 42.0 × 105cfu/ml while enteric bacterial counts on SS agar and MacConkey agar were 0.1 × 104 to 39.0 × 104cfu/ml and 0.3 × 103 to 3.5 × 104cfu/ml samples, respectively. Out of 74 isolates, 5 Gram-positive (22%) and 18 Gram-negative (78%) bacteria were randomly selected for detailed study. Bacillus was the dominant among the Gram-positive bacteria. Eighteen Gram-negative enteric isolates belonged to the genera Enterobacter (E. amnigenus and E. intermedium (44%), Alcaligenes (28%), Salmonella (17%), Escherichia (5.6%) and Plesiomonas) (5.6%). The NO3 – N, NO2 – N and phosphorus concentrations were found to be below the safety level from pollution point of view. BOD and COD values along with the presence of different bacteria clearly indicated that the River Buriganga was polluted with the organic, chemical and bacterial pollutants. Key words: Bacteria; Buriganga River; Enteric bacteria; Pollution; Bangladesh DOI: 10.3329/bjb.v38i1.5128 Bangladesh J. Bot. 38(1): 87-91, 2009 (June)